English Lecturers’ Perceptions on the Transition to Outcome-Based Education in Indonesia: Challenges and Adaptation - Rizky Prasetya; Fenti Sofiani (Faculty of Education and Teacher Training of UIN Palopo, 2025)
This study explores English lecturers’ perceptions of Outcome-Based Education (OBE), the challenges they face in its implementation, and the strategies they adopt to adapt their teaching practices. To investigate this issue, the study employed a mixed-methods approach, combining quantitative survey data from 78 English lecturers with qualitative insights from 15 semi-structured interviews. Thematic analysis of interviews provided in-depth perspectives on faculty struggles, adaptation mechanisms, and the role of institutional support. Findings indicate that while some lecturers appreciate the clarity and structure OBE brings to curriculum design, many report increased workloads, reduced teaching flexibility, and difficulties in applying rigid assessment rubrics to evaluate complex skills like critical thinking and literary analysis. However, lecturers who received targeted training and institutional backing expressed greater ease in aligning their teaching with OBE requirements. This research adds to existing studies on OBE by focusing on the perspectives of English lecturers, who are often overlooked in OBE discussions. It highlights the mismatch between standardized education reforms and the interpretive nature of English teaching. The findings suggest that policymakers and curriculum designers should avoid a one-size-fits-all approach and instead create OBE models that suit the needs of different disciplines.